Wunderlich syndrome as a rare complication of polyarteritis nodosa: a case report - D. Oliveira; A. Martins; F. Martins; M. Rato; F. Pinheiro; D. Fonseca; C. Vaz; E. Mariz; L. Costa (PAGEPress Publications, 2024)
Spontaneous subcapsular and perirenal hemorrhage, known as Wunderlich syndrome (WS), is a rare clinical manifestation of polyarteritis nodosa (PAN). We report a case of a 48-year-old male with a history of recurrent episodes of leg muscle tenderness and dysesthesia, bilateral flank pain, painful nodular skin lesions in the lower limbs, weight loss, and difficult-to-control arterial hypertension. The abdominopelvic computed tomography angiography showed a large left perirenal hematoma, leading to the patient's admission to the intensive care unit. After the exclusion of infectious or neoplastic foci, the patient was diagnosed with PAN and started intravenous methylprednisolone pulses with a good response. Since WS is a rare initial clinical manifestation of PAN, an early diagnosis and aggressive treatment will significantly improve clinical outcomes.